The ancient Roman afterlife : di manes, belief, and the cult of the dead - King, Charles (Professor of history) (Ashley and Peter Larkin series in Greek and Roman culture., 2020)
In ancient Rome, it was believed some humans were transformed into special, empowered beings after death. These deified dead, known as the manes, watched over and protected their surviving family members, possibly even extending those relatives' lives. But unlike the Greek hero-cult, the worship of dead emperors, or the Christian saints, the manes were incredibly inclusive--enrolling even those without social clout, such as women and the poor, among Rome's deities. The Roman afterlife promised posthumous power in the world of the living. While the manes have often been glossed over in studies of Roman religion, this book brings their compelling story to the forefront, exploring their myriad forms and how their worship played out in the context of Roman religion's daily practice. Exploring the place of the manes in Roman society, Charles King delves into Roman beliefs about their powers to sustain life and bring death to individuals or armies, examines the rituals the Romans performed to honor them, and reclaims the vital role the manes played in the ancient Roman afterlife